L´OEUVRE DE CHARITÉ, NOUVELLE ESPAGNOLE (1808) DE BOUFFL ERS - de Vicente-Yagüe Jara, Antonio José (Anales de Filología Francesa, 2008)
In 1808, Bouffl ers published L’OEuvre de charité, nouvelle espagnole in Mercure de France. As it happens with the rest of his tales or short stories published at the beginning of the 19th century, this story has a moral nature, as it deals with the education of the nobles in virtue and the reform of their corrupt habits, thus showing Bouffl ers’ conservative beliefs in his last years. Starting from the initial charity of a young lady towards a wounded man, Bouffl ers presents a beautiful story of friendship and love between two youngsters. The author takes pleasure in recalling the pleasant life prior to the Revolution and the utopian dream of the perfect couple. It is the message of social happiness that Bouffl ers is trying to put across.